Evaluation of Socioeconomic Status Indicators for Confounding Adjustment in Observational Studies of Medication Use. Issue 6 (25th February 2019) - Gopalakrishnan, Chandrasekar; Gagne, Joshua J.; Sarpatwari, Ameet; Dejene, Sara Z.; Dutcher, Sarah K.; Levin, Raisa; Franklin, Jessica M.; Schneeweiss, Sebastian; Desai, Rishi J.
Abstract : Methodologic research evaluating confounding due to socioeconomic status (SES) in observational studies of medications is limited. We identified 7, 109 patients who initiated brand or generic atorvastatin from Medicare claims (2011–2013) linked to electronic medical records and census data. We created a propensity score (PS) containing only claims‐based covariates and augmented it with additional claims‐based proxies for SES, ZIP code, and block group level SES. Cox models with PS fine‐stratification and weighting were used to compare rates of a cardiovascular end point and emergency department visits. Adjustment with only claims‐based variables substantially improved balance on all SES variables compared with the unadjusted. Although inclusion of SES in PS models further improved balance on SES variables compared with models with claims‐based covariates only, it did not materially change point estimates for either outcome. Inclusion of claims‐based proxies may mitigate confounding by SES when aggregate‐level SES information is unavailable.